Pembentukan Peraturan Kebijakan Berdasarkan Asas-Asas Umum Pemerintahan yang Baik - Suratno, Sadhu Bagas (Lentera Hukum, 2017)
The creation of policy is one of the prerogatives of a free and uninhibited (freies ermessen, or free discretion) government administrations. Although freies ermessen grants free authority to the government, within the framework of national the law said the government should still observe legislation and the Principles of Good Governance. However, at the implementation level, there are still many policies that which are difficult to put into effect due to ambiguous interpretation and conflicts of interest, thus resulting in legal uncertainty. Based on this, there needs to be an affirmation of the position taken by the Indonesian government regarding the contradictory relationship between written law and implementation, so as to ensure the appropriate application of the principles of freies ermessen. Keywords: Policy Rules, Freies Ermessen, Legislatin, Good Governance Principles